Pasteurella multocida: Molecular Biology, Toxins and Infection - Aktories, Klaus; Orth, Joachim Hans Christian; Adler, Ben (Current Topics in Microbiology and Immunology, 2012)
This volume brings together contributions from experts in the field of Pasteurella research. Its covers areas such as comparative genomics, pathogenic mechanisms, bacterial proteomics, as well as a detailed description and analysis of PMT and its interaction with host tissues, cells, immune system, and signalling pathways.